Pengaruh Weight Training Terhadap Power Otot Tungkai Atlet Rowing - Ananda Fadilah; Amanda Nurul Rika Azzahra; Indri Rahmatunisa; Muhammad Igo Prayoga; Ahmad Fua’din (Program Studi Pendidikan Olahraga STKIP Kie Raha Ternate, 2023)
Power is one of the important factors in rowing. Rowing athletesathletes need good leg power to push the oars strongly and quickly. Weight training is one of the training methods that can increase leg power. This study aims to determine the effect of weight training on leg power for rowing athletes. This research uses experimental method with a two group pretest posttest research design. Population The study population was male rowing athletes at the rowing club in Bandung. Sample The research sample was 13 athletes who were divided into two groups, namely the treatment group (6 athletes) and the control group (7 athletes). Treatment group (6 athletes) and control group (7 athletes). The treatment group was given weight training for 8 weeks, while the control group was given no weight training. Training without weight training. Measurement of leg power is done before and after treatment using the vertical jump test. The results showed that there is a significant effect of weight training on leg power. Limbs of rowing athletes. The treatment group's leg power value increased significantly after significantly after being given treatment, while the limb power value of the control group did not increase significantly. Because the treatment group and control group still do ergometer rowing exercises that use the legs. Limbs. Based on the results of this study, it can be concluded that weight training can increase the leg power of rowing athletes.